2017
DOI: 10.1093/treephys/tpx152
|View full text |Cite
|
Sign up to set email alerts
|

Reliance on deep soil water in the tree species Argania spinosa

Abstract: In South-western Morocco, water scarcity and high temperature are the main factors determining species survival. Argania spinosa (L.) Skeels is a tree species, endemic to Morocco, which is suffering from ongoing habitat shrinkage. Argan trees play essential local ecological and economic roles: protecting soils from erosion, shading different types of crops, helping maintain soil fertility and, even more importantly, its seeds are used by the local population for oil production, with valuable nutritional, medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
23
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 59 publications
0
23
0
1
Order By: Relevance
“…Whether shift in water resources can actually compensate for drought, impacts on plant physiology has not been well studied. As was expected, more groundwater and deep soil water acquisition during the dry season contributed to the maintenance of relatively higher photosynthesis activity in many tree species (Drake, Froend, & Franks, 2011;Zunzunegui et al, 2017), however, other studies have reported that shifts in water sources did not alleviate the effects of drought stress on tree gas exchange (Grossiord et al, 2017;Sun, Meng, Zhang, & Wan, 2011). Understanding the differences in water uptake patterns, stomatal control and their link between species could provide insights into ecological adaptation strategies and could be used to predict the dynamics of desert riparian species in fluctuating environments.…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…Whether shift in water resources can actually compensate for drought, impacts on plant physiology has not been well studied. As was expected, more groundwater and deep soil water acquisition during the dry season contributed to the maintenance of relatively higher photosynthesis activity in many tree species (Drake, Froend, & Franks, 2011;Zunzunegui et al, 2017), however, other studies have reported that shifts in water sources did not alleviate the effects of drought stress on tree gas exchange (Grossiord et al, 2017;Sun, Meng, Zhang, & Wan, 2011). Understanding the differences in water uptake patterns, stomatal control and their link between species could provide insights into ecological adaptation strategies and could be used to predict the dynamics of desert riparian species in fluctuating environments.…”
Section: Introductionmentioning
confidence: 66%
“…Stomata closure can reduce transpirational water loss but at the expense of restricting CO 2 diffusion into leaves during photosynthesis (Hetherington & Woodward, 2003;McDowell et al, 2008). As was expected, more groundwater and deep soil water acquisition during the dry season contributed to the maintenance of relatively higher photosynthesis activity in many tree species (Drake, Froend, & Franks, 2011;Zunzunegui et al, 2017), however, other studies have reported that shifts in water sources did not alleviate the effects of drought stress on tree gas exchange (Grossiord et al, 2017;Sun, Meng, Zhang, & Wan, 2011). As was expected, more groundwater and deep soil water acquisition during the dry season contributed to the maintenance of relatively higher photosynthesis activity in many tree species (Drake, Froend, & Franks, 2011;Zunzunegui et al, 2017), however, other studies have reported that shifts in water sources did not alleviate the effects of drought stress on tree gas exchange (Grossiord et al, 2017;Sun, Meng, Zhang, & Wan, 2011).…”
Section: Introductionmentioning
confidence: 84%
“…Plants in upland landscapes with thin soils may survive on water extracted from the weathered bedrock from below the soil, exploiting either groundwater (e.g., Miller et al, ) or rock moisture (sensu Salve et al, ; Rempe & Dietrich, ) from tens of meters below the ground surface (e.g., Anderson et al, ; Arkley, ; Bales et al, ; Eliades et al, ; Jones & Graham, ; Lewis & Burgy, ; Miller et al, ; Rempe & Dietrich, ; Rose et al, ; Sternberg et al, ; Zunzunegui et al, ; Zwieniecki & Newton, ). These and other previous studies in seasonally dry environments, however, have focused on local, site‐specific plant water use and have not explicitly addressed larger‐scale relationships between dominant vegetation patterns and the spatial availability of moisture beneath the soil.…”
Section: Introductionmentioning
confidence: 99%
“…Normally, plants preferentially absorb water from stable and continuous sources. For instance, deep-rooted species (e.g., trees and semi-arbors) can take up deeper water sources stably, enabling them to survive and tolerate seasonal water stress, i.e., go without rain for a long time [30][31][32][33][34]; in contrast, most shallow-rooted species (e.g., grasses and semi-shrubs) mainly depend on shallow soil water supplied by precipitation [19,[35][36][37][38][39][40]. The spatial complementarity of water sources causes niche segregation between species which make use of shallow and deep water, often referred to as the "two-layer hypothesis" [29,41].…”
Section: Introductionmentioning
confidence: 99%